Constructing interpretive inferences about literary text: The role of domain-specific knowledge. (April 2019) - McCarthy, Kathryn S.; Goldman, Susan R.
Abstract: Student readers struggle to construct the interpretive inferences necessary for successful literary comprehension. Expert think-alouds were conducted to identify the kinds of domain-specific knowledge that were drawn upon when reading the short story The Elephant . These data were used to construct three reading instructions provided to student (novice) literary readers. These instructions informed the student about two types of literary conventions (Rules of Notice, Rules of Signification, Combined). Analysis of the students' essays indicated having both types of domain-specific knowledge yielded the most interpretive inferences. Attention to language mediated the effect suggesting a means for domain-specific knowledge to be used to leverage student engagement in literary interpretation. Highlights: Successful literary reading requires the generation of interpretive inferences. Students do not readily construct these interpretive inferences. Experts rely on domain-specific knowledge of literary conventions to generate these inferences. Providing expert-like literary convention knowledge increases production of interpretive inferences.